Theoretical insight into effect of cation–anion pairs on CO2 reduction on bismuth electrocatalysts - Sun Hee Yoon (7179263) (2020)
This study presents theoretical insight into the mechanism of the CO2 reduction reaction (CO2RR) to formic acid (HCOOH) on Bi (0 1 2) surfaces in the presence of alkali metal cations (M+: Cs+, K+, and Li+) and/or halide anions (X−: Cl−, Br−, and I−) using density functional theory (DFT). The adsorption energy (Eads) and work function (Wf) of the anions increases with decreasing anion size (i.e., Cl− > Br− > I−). On the other hand, the larger the cation size is, the higher is the Eads (i.e., Li+ < K+ < Cs+) but the lower is the Wf (i.e., Cs+ < K+ < Li+). In the presence of the cation–anion pairs (M+/X−), Eads of the pairs on hydrated Bi (Bi-2H) becomes more negative than that in the cases of anions or cations alone, particularly when the ionic radius of the paired cation and anion do not differ significantly. Such a synergistic effect of the mixed ions is also observed for the work function values. In the case of anions alone, CO2 molecules prefer to coordinate directly with hydrated Bi atoms via the oxygen bidentate mode; in the case of cations alone, CO2 molecules directly bind to the cations via the oxygen monodentate mode, rather than the hydrated Bi atoms. Between two possible CO2RR pathways involving *OCHO and *COOH intermediates on Bi-2H pre-adsorbed with M+/X−, the former pathway requires less energy for all M+/X− pairs. In addition, cascaded reaction profiles from CO2* to HCOOH are obtained with Cs+/Cl− and K+/Cl− pairs in the former. This indicates that once CO2 is adsorbed, the following reactions proceed spontaneously on Bi-2H with Cs+/Cl− or K+/Cl− pairs. This study thus shed light on the positive effects of supporting electrolytes (e.g., CsCl and KCl) on catalytic CO2RR. Other Information Published in: Applied Surface Science License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.apsusc.2020.147459